1962
DOI: 10.1017/s0016756800057265
|View full text |Cite
|
Sign up to set email alerts
|

Clay Mineralogy of Selected Clays from the English Wealden

Abstract: X-ray analyses of selected samples from the argillaceous subdivisions of the English Wealden indicate that illite, kaolinite, and mixed-layer structures are present in variable amounts. The clay mineral assemblage is thought to reflect parent material, weathering conditions in the source area, and possibly some degrading of the illite structure by the action of active waters in the depositional environment. The specific clay minerals are tentatively correlated with the palaeogeographical framework proposed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The results of the XRD clay mineralogical analysis show that illite (ca 53%), kaolinite (ca 31%), illite-montmorillonite (10%), vermiculite (ca 5%) and illite-smectite (ca 1%) are the clay minerals present within the two formations ( The degradation of illite to structures similar to vermiculite and montmorillonite in the Ashdown and Wadhurst Clay formations has been previously suggested by Tank (1962). In this present study, illite-montmorillonite is observed in significant quantity as one of the mixedlayer minerals in the lower Ashdown and upper Wadhurst Clay formations.…”
Section: Clay Mineralsmentioning
confidence: 71%
See 3 more Smart Citations
“…The results of the XRD clay mineralogical analysis show that illite (ca 53%), kaolinite (ca 31%), illite-montmorillonite (10%), vermiculite (ca 5%) and illite-smectite (ca 1%) are the clay minerals present within the two formations ( The degradation of illite to structures similar to vermiculite and montmorillonite in the Ashdown and Wadhurst Clay formations has been previously suggested by Tank (1962). In this present study, illite-montmorillonite is observed in significant quantity as one of the mixedlayer minerals in the lower Ashdown and upper Wadhurst Clay formations.…”
Section: Clay Mineralsmentioning
confidence: 71%
“…Vermiculite is absent at West Hoathly (lower Wadhurst Clay Formation) while illite‐smectite is not present at Rock‐a‐Nore (lower Ashdown Formation). The degradation of illite to structures similar to vermiculite and montmorillonite in the Ashdown and Wadhurst Clay formations has been previously suggested by Tank (). In this present study, illite‐montmorillonite is observed in significant quantity as one of the mixed‐layer minerals in the lower Ashdown and upper Wadhurst Clay formations.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Mitchell & Taka (1984) have demonstrated that weathered micas fall apart when their K 2 O content gets to 4 5%, so they would never occur as detritus with K 2 O values less than this. Detailed investigations suggest that this young component is an interstratified illite-smectite clay mineral in the Oxford Clay (Weir (Scotchman, 1987a) and a vermiculite in the Wealden (Tank, 1962). Its age is likely to approximate to the chronostratic age of the sample.…”
mentioning
confidence: 92%